2009
DOI: 10.1186/1476-7120-7-14
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in evaluation of post-interventional femoral vein obstruction: a case report

Abstract: Ultrasound is the preferred imaging modality in diagnosis of vascular complications following cardiac catheterization and intervention. In some cases, however, bleeding surrounding the femoral vessels, may severely distort the color Doppler images, making detection of venous complications especially difficult. This report refers to such a case where post-catheterization haematoma was suspected to cause an obstruction of the femoral vein. Spectral Doppler recordings of blood flow in the common femoral vein, up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…20 It is a practical tool to assist the visualization of blood vessels in clinical practice, and it has been applied to PICC cannulation 21 and deep vein catheterization. 22,23 We took the advantages of color Doppler ultrasound long-axis display for in-plane guided cannulation in upper extremity AVF. Our data demonstrated that ultrasonic-assisted improved the one-time cannulation success rate and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 It is a practical tool to assist the visualization of blood vessels in clinical practice, and it has been applied to PICC cannulation 21 and deep vein catheterization. 22,23 We took the advantages of color Doppler ultrasound long-axis display for in-plane guided cannulation in upper extremity AVF. Our data demonstrated that ultrasonic-assisted improved the one-time cannulation success rate and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler ultrasound can clearly and dynamically display the inner diameter, depth, direction, branches, and blood flow of blood vessels, which is widely used in the assessment of patients' blood vessels 20 . It is a practical tool to assist the visualization of blood vessels in clinical practice, and it has been applied to PICC cannulation 21 and deep vein catheterization 22,23 . We took the advantages of color Doppler ultrasound long‐axis display for in‐plane guided cannulation in upper extremity AVF.…”
Section: Discussionmentioning
confidence: 99%